2013
DOI: 10.1007/s10384-013-0292-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of axial length on ganglion cell complex (GCC) thickness and on GCC thickness to retinal thickness ratios in young adults

Abstract: GCC thickness is affected by axial length. Because the prevalence of myopia is high in Japan, when determining the GCC thickness of Japanese individuals, it seems necessary to consider the axial length as well. To take account of individual variation in axial length, we propose the ratio parameters as a suitable parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
34
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
5
34
4
Order By: Relevance
“…Although the data of each database in the RS-3000 SD-OCT instrument have not been published, our results suggest that the lower limit of the normal mGCC thickness in the highly myopic database is thinner than that in the non-highly myopic database. Earlier studies reported that the mGCC thickness in normal eyes without correction of the AL-related magnification was significantly and inversely correlated with the AL [17,35,36]. Our results agree with these earlier results that normal eyes with longer ALs (i.e., highly myopic eyes) have thinner mGCC.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Although the data of each database in the RS-3000 SD-OCT instrument have not been published, our results suggest that the lower limit of the normal mGCC thickness in the highly myopic database is thinner than that in the non-highly myopic database. Earlier studies reported that the mGCC thickness in normal eyes without correction of the AL-related magnification was significantly and inversely correlated with the AL [17,35,36]. Our results agree with these earlier results that normal eyes with longer ALs (i.e., highly myopic eyes) have thinner mGCC.…”
Section: Discussionsupporting
confidence: 95%
“…These results indicate that evaluation of the GCC thickness by averaging a wider area is not the optimal method, especially for eyes with early glaucoma. It would be better to evaluate the mGCC thickness by combining it with another method of analysis such as asymmetry analysis [34,[37][38][39], or other parameters that represent focal GCC alterations with less influence by high myopia [36,40].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that AXL was negatively associated with GCC thickness in normal eyes [19, 20]. Regarding our results, we speculate that retinal layers in eyes with longer AXL that were tangentially stretched by globe elongation may have little capacity to increase after cataract surgery.…”
Section: Discussionsupporting
confidence: 55%
“…[15][16][17][18] The thicknesses of the retinal nerve fiber layer (NFL), ganglion cell layer (GCL), and inner plexiform layer (IPL) were reported by some authors to be thinner in myopic eyes compared to normal eyes. 19 Furthermore, the thickness of the outer retinal layers, including the retinal pigment epithelium (RPE) and the photoreceptor layer, vary according to the axial length (AL). 20 However, the results of the above studies are controversial because the characteristic of macular intraretinal layer thickness in myopia remains unclear.…”
mentioning
confidence: 99%